Implementation of Umkm Model Canvas Concept at Pt. Variegrow Inovasi Pertanian - Satria, Hardiat Dani (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2024)
PT. Variegrow Inovasi Pertanian is a Micro, Small, and Medium Enterprise (MSME) that emphasizes agricultural innovation. Established in 2021, this MSME has received several national awards for its innovative aspects. The aim of this research is to analyze the implementation of the UMKM Model Canvas concept at PT. Variegrow Inovasi Pertanian. This study adopts a descriptive qualitative approach. Data collection methods include observation, interviews, and documentation. Based on observations and secondary data analysis from PT. Variegrow Inovasi Pertanian, it is found that this enterprise was founded with limited capital of less than Rp.5,000,000. The enterprise has survived due to receiving significant mentoring support from local government, private institutions, and even ministries. This knowledge support has enabled PT. Variegrow Inovasi Pertanian to improve its management, marketing strategies, and business legality. The unique and innovative products of PT. Variegrow Inovasi Pertanian are the key to survival in the market competition. In conclusion, this research indicates that PT. Variegrow Inovasi Pertanian has implemented several UMKM Model Canvas concepts in its business, although there are still many shortcomings. The spirit of innovation dominates the enterprise. The recommendation from this research is the necessity of a strong sales strategy to ensure the products of PT. Variegrow Inovasi Pertanian can thrive in the market.